CDC Perspective an a Dynamic Partnership to Improve the Surveillance of COPD at State and Local Levels - Croft, Janet B. (Lung Health Prof Mag, 2013)
The Centers for Disease Control and Prevention (CDC) has long recognized that its major constituents, the state and local health departments, have the primary role for targeting resources and efforts to prevent and control disease. However, state and local level information about disease burden may be more relevant to local and state decision-makers than national disease estimates. Until November 2012, there were no widely available state level prevalence estimates for chronic obstructive pulmonary disease (COPD) with the exception of a few states that had collected their own prevalence data.